Dynamics of the Salivary Microbiome During Different Phases of Crohn's Disease - Zhang, Tianyu; Kayani, Masood ur Rehman; Hong, Liwen; Zhang, Chen; Zhong, Jie; Wang, Zhengting; Chen, Lei (Frontiers in Cellular and Infection Microbiology, 2020)
Crohn’s disease is a chronic disorder that typically affects the gastrointestinal tract. The increased incidence in the recent years, especially in Asian countries, prompts for performing studies and gain newer insights into the etiology and pathogenesis of the disease. Among other causative factors, gut microbiome and its cross-talk with the salivary microbiome is a known factor that has a plausible role in the pathogenesis of Crohn’s disease. The gut microbiome has been extensively studied, however, the salivary microbiome and its dynamics during different phases of this disease remain understudied. In this study, we obtained saliva samples from the patients during active and remission phases of the disease and compared them with control samples and highlighted the differences in taxonomic as well as predicted functional pathways among them. Our results indicated that the α and β diversities were significantly lower during the active phase in contrast with remission phase and healthy samples. In general, Firmicutes were most abundant among the three sample groups, followed by Bacteroidetes and Proteobacteria. Genus level distribution highlighted Streptococcus, Neisseria, Prevotella, Haemophilus, and Veillonella as the five most abundant taxa. Differential abundance analysis of the three sample groups identified significant enrichment of 30 bacterial taxa in the active phase that included g_Prevotella, f_Prevotellaceae, and p_Bacteroidetes. Furthermore, remission phase and control also exhibited significant enrichment of 24 and 22 bacterial taxa, respectively. 11 differentially abundant pathways were also identified, 4 were significantly enriched in healthy controls whereas other 7 were significantly enriched in active phase of the disease. Several important pathways, such as ribosome biogenesis and Energy metabolism were depleted in the active phase. Our study has highlighted several taxa and functional categories that could be implicated with the onset of Crohn’s disease and thus have the potential to serve as biomarkers of the active disease. However, these findings require further validation through functional studies in the future.